Linking shadow economy and CO2 emissions in Nigeria: Exploring the role of financial development and stock market performance. Fresh insight from the novel dynamic ARDL simulation and spectral causality approach - Yu, Yang; Chukwuma Onwe, Joshua; Jahanger, Atif; Adebayo, Tomiwa Sunday; Hossain, Md. Emran; David, Ali (Frontiers in Environmental Science, 2022)
First and foremost, the present study seeks to traverse the informal sector characterized by shadow economy in the presence of financial development, economic growth and stock market performance on environmental pollution in Nigeria from 1981 to 2019. The dynamic autoregressive distributed lag (DARDL) approach was employed to measure the short and long-run elasticities, while the spectral causality is applied to categorize the causal directions. Findings from the study revealed that structural break unit root test revealed that all variables are stationary at first difference. The ARDL bound test confirmed the existence of long-run association among the employed variables. The ARDL long run results reveals that economic growth, financial development and stock market performance are significantly responsible for carbon emission in Nigeria while, shadow economy significantly improves environmental quality in Nigeria. Findings from the spectral causality results finds a unidirectional causal relationship from financial development, economic growth, trade, stock market performance and shadow economy to carbon emission in Nigeria. The empirical findings of this study give some perceptive policy recommendations to overcome the adverse effect of carbon emission in the environment.